Evaluating the Utility of the Surprise Question Among General Physicians for Appropriate Palliative Care Indication in Brazil - Gabriel Barros Furtado Leão Borges; Cristiane Bitencourt Dias (Palliative Medicine Reports)
Objectives: This study aimed to assess the agreement between established tools, such as the Palliative Performance Scale (PPS) and Brazilian version of the Supportive and Palliative Care Indicators Tool (SPICT-BR), and the subjective assessment of palliative care (PC) need using the Surprise Question (SQ) administered by resident physicians. This assessment was conducted among hospitalized patients, with and without cancer, to determine the efficacy of these tools in indicating the need for PC. Methods: A six-month cross-sectional study in 2019 of medical records of patients hospitalized in a single center in IAMSPE-Brazil. The SPICT-BR and PPS were applied to the medical record data, and the SQ was posed to each resident physician. Comparisons for categorical data were made using the chi-square test, with p < 0.05 considered statistically significant. Results: Of 203 patients evaluated, 57.6% were male and 81.2% were older adults (≥60 years). The mean age was 67.40 ± 9.72 years. Chronic disease was nonneoplastic in 78.32% of patients, and 56.65% had not been hospitalized in the preceding year. The PPS score was <70% in 69.4% of patients, and 51.2% met at least one SPICT-BR criterion. Among patients with cancer, 40.9% had over two positive SPICT-BR criteria; 97.5% of these patients received NO responses to SQ by residents (p < 0.0001). Similarly, 90.6% of patients with one SPICT-BR criterion received NO responses to SQ, with no significant difference between groups. Conclusion: The SQ proved to be a valuable tool for PC indication, particularly when administered by untrained professionals. Consistent with SPICT-BR findings, our study highlights the SQ’s role in facilitating early identification of patients in need of PC.